Improvement of treatment methods of combined traumas of maxillofacial region - V.V. Shamov; A.A. Kholikov; D.R.Fattayeva (Periodica Journal, 2022)
Improvement of methods of diagnostics and treatment of concomitant traumas of the maxillofacial region should be aimed at improving the quality of diagnosis for more accurate planning of surgery, reduction of traumatization during surgery, acceleration of rehabilitation period
Keywords: traumas of maxillofacial region; combined traumas; maxillofacial surgery